managemnet of rural development projects. - Boraian, M.P.
The author describes that rural development enjoy top most priority in the policies and programmes of developing countries including India. Designing and execution of development projects is an essential means of attaining certain basic objectives such as generation of employment, alleviation of poverty, provision of healthcare, liquidation of illiteracy, and fulfilment of housing and other basic needs in rural areas. In this concern the auther project planning and its implementation by various developing countries have immense contribution towards the endorsment of natural wealth, human resources and establishment of infrastructural facilities. Therefore, effecient management of projects, gains inereased emph
Keywords: Projects; Management; Rural Development